Implementing TQM for library services : the issues. - ROWLEY, Jennifer (1996)
Defines TQM, and presents the main elements. Explores some of the issues that need to be addressed if TQM is to be successfully implemented, viz: defining quality; clarifying customers; establishing quality as a strategic issue; organizational structure; organizational culture; and, human resource management. Notes that all services present particular problems in relation to quality management because of their inherent characteristics intangibility, perishability, simultaneity and heterogeneity. On the other hand there is an increasing focus on the importance of the quality of the service.